PPARs in Irradiation-Induced Gastrointestinal Toxicity - Christine Linard; Maâmar Souidi (PPAR Research)
The use of radiation therapy to treat cancer inevitably involves exposure of normal tissues. Although the benefits of this treatment are well established, many patients experience distressing complications due to injury to normal tissue. These side effects are related to inflammatory processes, and they decrease therapeutic benefit by increasing the overall treatment time. Emerging evidence indicates that PPARs and their ligands are important in the modulation of immune and inflammatory reactions. This paper discusses the effects of abdominal irradiation on PPARs, their role and functions in irradiation toxicity, and the possibility of using their ligands for radioprotection.